Study Of Flood Control And Reliability Index Of Tanggul River - Giyanto - -; Dhemi Harlan; Suardi Natasaputra (Jurnal Teknik Sipil, 2019)
AbstractTanggul River which is located in Jember Regency, East Java Province, experiences floods every year. Increasing in flood discharge, decreasing on river capacity and lowing of slope cause flooding. In this study, we will analyze Tanggul River in full bank capacity condition with flood discharges for the return period of 2, 5, 10, 20 and 25 years, and then analyze flood control scenario, reliability index and economic feasibility. Flood control are carried out structurally by river normalization, side overflow construction, embankment elevation and a combination of the three activities. 1-dimensional and 2-dimensional hydraulic analysis use HEC-RAS software version 5.06, reliability index analysis uses the Safety Factor (SF) and First-Order Second Moment (FOSM) methods, and economic feasibility uses the Benefit Cost (B / C) Ratio method. The benefit component is reducting from flood inundation which is analyzed by QGIS software and Open Street Map (OSM), while the cost component is flood control construction costs. Based on the results of the study, the river embankment full bank capacity conditions correspond to floods return period of 5 years, recommended flood control are river normalization and elevation of the embankment with a B / C Ratio value of 1.7, flood reduction 62.88%, reliability index SF method 1.07 and FOSM method 97.05%AbstrakSungai Tanggul terletak di Kabupaten Jember Provinsi Jawa Timur mengalami luapan banjir setiap tahun. Adanya peningkatan debit banjir, penurunan kapasitas sungai dan kemiringan yang landai diduga menjadi penyebab luapan banjir. Pada kajian ini akan menganalisis Sungai Tanggul kondisi full bank capacity dengan debit banjir rencana periode ulang 2, 5, 10, 20 dan 25 tahun, selanjutnya menganalisis skenario pengendalian banjir, indeks kehandalan dan kelayakan ekonomi. Upaya pengendalian banjir dilakukan secara struktural dengan normalisasi sungai, pembangunan pelimpah samping, peninggian tanggul dan kombinasi dari ketiga kegiatan tersebut. Analisis hidrolika 1 dimensi dan 2 dimensi menggunakan software HEC-RAS versi 5.06, analisis indeks kehandalan dengan metode Safety Factor (SF) dan First-Order Second Moment (FOSM), dan analisis kelayakan ekonomi dengan metode Benefit Cost (B/C) Ratio. Komponen benefit berupa pengurangan genangan banjir yang dianalisis dengan software QGIS dan Open Street Map (OSM), sedangkan komponen cost berupa biaya konstruksi pengendalian banjir. Berdasarkan hasil kajian, diperoleh kapasitas Sungai Tanggul kondisi full bank capacity yang bersesuaian dengan banjir periode ulang 5 tahun, upaya pengendalian banjir yang direkomendasikan berupa normalisasi sungai dan peninggian tanggul dengan nilai B/C Ratio 1,7, reduksi banjir 62,88 %, Indeks kehandalan metode SF 1,07 dan metode FOSM 97,05%.